Chalenges and opportunities brought by foreign direct investments in Brazil - Carvalho, Eveline Barbosa Silva; Serra, Renata; Zourabichivili, Alexandre (Internext, 2008)
This paper analyzes the challenges and opportunities brought by foreign direct investment in general and in Brazil particularly. The study is based on literature review and statistical data show that foreign direct investments have important effects on the business environment of the host country as they bring productivity improvement, formal employment and income generation, increase on the export level, establishment of firms with high innovation standards and the capacity to improve the quality of national products, with some degree of technology diffusion, increases in the network of suppliers and possible buyers, and the introduction of new strategies of business management, logistics as well as other ways of modernizing industrial structures. It concludes that the major benefits from foreign direct investments are the change on local companies strategies. The study also shows that investments are concentrated on most developed areas and that there is no specific strategy for investment attraction to the less economically favored areas of Brazil.